Preparation method of cement concrete back scattering electron image analysis sample
By employing steps such as terminating hydration and low-temperature drying, pre-grinding, vacuum cold mounting, coarse grinding, fine grinding, and polishing, the problem of microcracks caused by lubricant softening during the preparation of cement concrete samples was solved, ensuring high-quality backscattered electron image analysis.
Patent Information
- Application Number
- CN202511425871.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-30
- Publication Date
- 2025-11-07
Smart Images

Figure CN120908225A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of building material test analysis, and particularly relates to a sample preparation method for cement concrete backscattered electron image analysis. BACKGROUND
[0002] Cement concrete, as the most widely used civil engineering material in the world, supports the infrastructure construction in many fields such as building, transportation and water conservancy. However, the production process of cement concrete consumes a large amount of energy and emits carbon dioxide, and the resource consumption and environmental impact during the use stage are also significant. Under the background of the strategy of “carbon peak and carbon neutrality”, energy saving and emission reduction and green transformation of the cement concrete industry have become a key issue, and in-depth study of its microstructure (such as hydration degree, hydration product characteristics, pore structure and interface transition zone characteristics) is the core foundation for optimizing formula, improving performance and reducing environmental load, which makes the reliability of microanalysis technology even more important. In the study of the microstructure of cement concrete, the scanning electron microscope backscattered electron image analysis method has become a mainstream technical means because it can directly show the micro-morphology and composition difference. However, this method has very high requirements for the flatness and smoothness of the sample surface, and a special preparation process is needed to obtain a sample that meets the analysis standards. At present, the industry generally adopts the preparation process of “resin cold inlay-grinding-polishing”: first, the cement concrete sample is cold inlaid with resin to avoid sample fragmentation during subsequent processing; then, the surface impurities and defects are removed through multiple grinding processes to preliminarily flatten the sample; finally, polishing treatment is carried out to ensure that the surface roughness meets the requirements of backscattered electron imaging, providing a basis for subsequent image analysis. However, the existing “resin cold inlay-grinding-polishing” method has obvious defects in actual operation: a large amount of lubricant (such as coolant) and solvent is needed in the grinding and polishing process to reduce frictional heat and clean the grinding debris, and these liquids can easily penetrate into the interior of the cement concrete sample, causing the sample matrix to soften. The softened sample is easily cracked in the subsequent polishing process due to the pressure and friction of the polishing pad, and even macroscopic cracks can occur, which not only destroys the original microstructure of the sample, but also causes false images in the backscattered electron image, interfering with the accurate identification of key information such as hydration products and pore structure, seriously affecting the reliability of the analysis results, and making it difficult to meet the needs of high-precision microstructure research. SUMMARY
[0003] The present application aims to provide a sample preparation method for cement concrete backscattered electron image analysis to solve the technical problem that the backscattered electron image analysis sample prepared by the prior art is easily cracked in the polishing process due to the softening of the sample by lubricant and solvent, thereby reducing the accuracy of the analysis results.
[0004] To achieve the above object, the technical scheme adopted by the present application is as follows: A sample preparation method for cement concrete backscattered electron image analysis, comprising the following steps: S1, obtaining a sample: sampling and crushing the cement concrete to an appropriate size to obtain a sample; S2, terminating hydration and low-temperature drying: placing the sample obtained in S1 in anhydrous ethanol or isopropanol for immersion and low-temperature drying; S3, pre-polishing: pre-polishing the dried sample in S2 using coarse sandpaper; S4, inlaying: inlaying the pre-polished sample in S3 with low-viscosity epoxy resin in a vacuum cold inlaying device; S5, rough grinding: sequentially using 800#, 1200#, 1500# and 2000# sandpaper to polish the sample after the epoxy resin in S4 is cured; S6, secondary low-temperature drying: wiping the polished sample in S5 with anhydrous ethanol and then low-temperature drying; S7, fine grinding: sequentially using 2500#, 3000# and 4000# sandpaper to finely grind the dried sample in S6; S8, polishing: sequentially using 1000 nm and 500 nm polishing liquid to polish the finely ground sample in S7; S9, final cleaning: wiping the polished sample in S8 with anhydrous ethanol to obtain a backscattered electron image analysis sample with a smooth and flat surface.
[0005] The principle and advantages of the present application are as follows: 1. Compared with the cement concrete backscattered electron image sample prepared by the prior art, which is prone to cracking and results in low accuracy of the analysis results, the present application can avoid cracking of the cement concrete sample in the traditional method by sequentially processing the cement sample through "terminating hydration and low-temperature drying-pre-polishing-inlaying-rough grinding-secondary low-temperature drying-fine grinding-polishing-final cleaning", thereby obtaining a smooth, flat, scratch-free and crack-free sample, and further obtaining a high-quality backscattered electron image. Specifically, first, the present application carefully obtains and cleans the sample through pretreatment (including sampling in S1, terminating hydration and low-temperature drying in S2, and pre-polishing in S3), thereby avoiding the introduction of new damage; second, in the inlaying in S4, the "vacuum+low-viscosity epoxy resin+cold inlaying" three-in-one mode fundamentally strengthens the brittle porous sample and bonds the internal micro-cracks, thereby achieving core reinforcement and laying the foundation for "crack resistance". Subsequently, through the gradual progressive finishing of rough grinding in S5, secondary low-temperature drying in S6, fine grinding in S7 and polishing in S8, through the steps of coarse to fine grinding and polishing, each step only creates better conditions for the next step, gradually reduces the mechanical stress and thermal stress in a large range to the minimum, and finally obtains a stress-free and scratch-free surface.
[0006] 2、This scheme can quickly trim the shape, expose the target area and provide a better mechanical bonding surface for inlaying by pre-grinding the sample before inlaying.
[0007] 3、This scheme can achieve the following effects by inlaying the pre-ground sample in S3 with low viscosity epoxy resin in a vacuum cold inlaying device: (1) reinforcement and support: cement concrete is brittle, porous and contains hard aggregates. The inlaying resin wraps it into a whole, providing mechanical support for the brittle sample and greatly enhancing the strength of the sample to prevent it from breaking in the subsequent grinding and polishing process. (2) Edge protection: during polishing, the edge of the sample is the most vulnerable area and is most likely to peel off or produce "comet tail" scratches. After resin wrapping, the sample and resin form a unified polishing surface, and the edge is protected by tough resin, thus obtaining clear and complete edge information. (3) Vacuum degassing: concrete samples are porous and contain air in the pores. Inlaying in a vacuum environment can extract air from the pores and allow low viscosity epoxy resin to fully penetrate every pore and microcrack in the sample. This plays the role of "glue" to bond the internal microstructure together, effectively preventing the expansion of these original microcracks under stress, and preventing polishing liquid and abrasive particles from entering the pores to avoid contamination and subsequent peeling. (4) Cold curing: the use of room temperature or low temperature curing epoxy resin avoids the thermal stress caused by heating and cooling in the heat inlaying process, which is the main cause of sample cracking.
[0008] 4、This scheme uses low-temperature drying after cleaning agent soaking or scrubbing during the entire cleaning process, not only effectively removing loose particles, contaminants or abrasive debris and / or lubricants left over from the previous process, but also protecting the sample's microstructure. Specifically, low-temperature drying (such as 40-60°C) is to gently remove the solvent to avoid the rapid evaporation of internal moisture or the generation of thermal stress caused by high temperature, which can cause microcracks, further improving the structural integrity of the sample and the accuracy of the analysis results.
[0009] 5、This scheme sets up a secondary low-temperature drying step between S5 coarse grinding and S7 fine grinding, effectively and completely removing the abrasive particles left over from the previous process to prevent cross-contamination. Specifically, coarse grinding produces a large amount of abrasive and sample debris of different particle sizes. If these particles are brought into the next finer grinding step, they will become huge "abrasives" that will pull out deep and long scratches on the surface, which are extremely difficult to remove in the later stages and are the main cause of substandard sample surface quality. Reusing anhydrous ethanol can effectively remove these particles without damaging the sample.
[0010] Preferably, as an improvement, in S1, the sample is a block sample, the thickness of the block sample is less than 10 mm, and the length and width of the block sample are both less than 15 mm.
[0011] Technical effects: The above arrangement facilitates faster and more complete replacement of air in the pores during subsequent inlaying and filling with resin. This ensures that the internal structure of the sample is firmly reinforced by the resin, greatly reducing the risk of internal cracking or peeling during subsequent grinding and polishing due to insufficient internal support.
[0012] Preferably, as an improvement, in S2, the soaking time is 5-7 days, and the ethanol or isopropanol is replaced on the first day and the third day.
[0013] Technical effects: The above arrangement facilitates complete termination of the cement hydration reaction and complete replacement of moisture in the sample pores, while avoiding destructive stress during the drying process. The hydration of cement particles is a continuous and slow process, and even if the sample is broken, the unhydrated cement particles inside will continue to react once they come into contact with moisture. The purpose of using anhydrous ethanol or isopropanol is to replace the moisture by taking advantage of their non-reactive properties with cement. However, the initial liquid in the sample pores is water, and short-term soaking can only replace the surface moisture, leaving the internal core still in a water environment. The long soaking time of 5-7 days in this scheme ensures that the solvent has enough time to gradually penetrate to the core area of the sample through diffusion, replacing all the moisture inside, thereby fundamentally and permanently terminating any possible hydration reaction and protecting the original microstructure of the sample. Replacing the fresh solvent on the first and third days based on the diffusion principle and concentration gradient efficiently replaces the pore liquid, ensuring that the moisture in the sample internal pores is completely replaced. Long-term experiments by the inventors have found that if the soaking time is too short or the solvent is not replaced during the process, the hydration termination is not complete, the cement hydration continues, resulting in errors in the hydration degree test and increasing the risk of cracking.
[0014] Preferably, as an improvement, in S2, the low-temperature drying is all performed in a low-temperature oven, the drying temperature is 40-60℃, and the drying time is 12-24h.
[0015] Preferably, as an improvement, in S6, the low-temperature drying is all performed in a low-temperature oven, the drying temperature is 40-60℃, and the drying time is 4-6h.
[0016] Technical effects: The above-mentioned setting is adopted to facilitate gentle evaporation and eliminate capillary stress. The sample pores have been completely filled with anhydrous ethanol or isopropanol. Although the boiling points of these solvents (ethanol 78℃, isopropanol 82℃) are not high, the low temperature of 40-60℃ is far below the boiling point, ensuring that the solvent is removed slowly by evaporation rather than "boiling", effectively avoiding the generation of bubbles during boiling, which may cause the internal pressure to crack the fragile cement structure and cause microcracks, thereby reducing the accuracy of the analysis results. The applicant has found through long-term experiments that if the drying temperature is too high, the sample may crack and microcracks due to the decomposition of part of the hydration products such as calcium vanadinite; and if the drying temperature is too low, the inlay effect will be poor due to insufficient drying.
[0017] Preferably, as an improvement, in S3 pre-polishing, the coarse sandpaper has a grade lower than 800#; the pre-polishing exposes the area of interest in the sample and obtains a larger flat surface.
[0018] Technical effects: The above-mentioned setting is adopted to facilitate rapid grinding of sharp protrusions and irregular shapes generated during sample breaking, significantly improving sample preparation efficiency. If sandpaper with a grade higher than 800# is used for pre-polishing, on the one hand, the small abrasive particles of fine sandpaper will reduce the pre-polishing efficiency; on the other hand, the surface obtained by polishing with fine sandpaper has a shallow inlay depth with epoxy resin during the inlay process, which cannot exert the supporting effect of epoxy resin on the sample, resulting in particle shedding or crack generation during subsequent polishing and affecting the accuracy of the analysis results.
[0019] Preferably, as an improvement, in S4 inlaying, the low-viscosity epoxy resin includes any one of EpoThin2, EpoKwick, EpoxiCure; when used, the curing system is prepared according to the ratio of epoxy resin: curing agent as 100:40-50.
[0020] Technical effects: The cement concrete is full of micron-level or nanometer-level pores and micro-cracks. The low-viscosity resin is used in the scheme, which can effectively penetrate into the extremely fine channels under the assistance of vacuum negative pressure, play a role of bonding and supporting for the sample, greatly enhance the mechanical strength of the sample itself, and prevent the sample from cracking from the inside during polishing. The low-viscosity epoxy resin can also improve the air removal effect in the sample, thereby minimizing the residual bubbles in the inlay, effectively avoiding bubbles becoming holes after polishing and producing interference signals in the BSE image, and reducing the accuracy of result analysis. In addition, the low-viscosity epoxy resin system has a relatively low curing shrinkage rate after optimized proportioning, and the smaller shrinkage means that the tight stress applied to the wrapped sample is also smaller, reducing the risk of sample cracking or debonding with the resin. If high-viscosity resin is used, the resin cannot enter the sample micropores due to its high viscosity, and the sample cannot be reinforced from the inside, which is easy to crack from the inside during polishing. In addition, the high-viscosity resin cannot expel the air, and there will be a large number of bubbles in the inlay and around the sample. These bubbles will be exposed as holes after polishing. In addition, the high-viscosity epoxy resin cannot fully penetrate the junction between the sample and the resin, resulting in insufficient edge support, and the aggregates or paste on the edge of the sample are easy to be "pulled out" and fall off during polishing, forming holes, cracks and micro-cracks, thereby reducing the accuracy of sample analysis results.
[0021] Preferably, as an improvement, in S5 rough grinding, the purpose of 800# sandpaper is to grind off a layer of epoxy resin on the surface to expose the pre-polished surface of the sample. The polishing time is determined according to the thickness of the epoxy resin on the surface of the sample; the polishing time of 1200#, 1500# and 2000# sandpaper is 30-60s, and the force of the pressure rod acting on the surface of the sample is 10-20N.
[0022] Technical effects: The above-mentioned setting is adopted, which facilitates efficient and controllable removal of the deep damage layer left by pre-polishing, and establishes a more and more fine scratch system, lays a perfect foundation for subsequent polishing, and any deviation of the parameters will magnify the problem and pass it on to the final step. The grinding and polishing time of 800# sandpaper is determined according to the thickness of the sample surface resin. If the grinding and polishing time is too short and / or the force acting on the sample surface pressure rod is too small, the resin layer will not be completely removed, and the subsequent step will still be grinding the resin, while the sample surface is hardly touched, resulting in that the sample will be lower than the resin plane after final polishing, and the sample cannot be observed. If the grinding and polishing time is too long or the force acting on the sample surface pressure rod is too large, the sample itself will be ground too much, leaving less space for subsequent grinding. 1200#, 1500# and 2000# sandpaper polishing aims to eliminate the coarse scratches introduced in the previous step. If the grinding time is too short or the force acting on the sample surface pressure rod is too small, the coarse scratches introduced in the previous step cannot be removed. If the grinding time is too long or the force acting on the sample surface pressure rod is too large, too much sample layer with resin support will be ground, resulting in hole and cracking.
[0023] Preferably, as an improvement, in the fine grinding in S7, no anhydrous ethanol or oil is added during the fine grinding process with 2500#, 3000# and 4000# sandpaper, the grinding time is 30-60 s, and the force acting on the sample surface pressure rod is 10-20 N.
[0024] Technical effects: The above-mentioned setting is adopted, which facilitates thorough elimination of all fine scratches and deformation layers left by coarse grinding, and creates a nearly perfect starting point for polishing. The "dry grinding" without using lubricant ensures that each abrasive grain of these fine sandpapers can effectively perform micro-cutting, efficiently removing the scratches left by the previous 2000# sandpaper. This scheme can effectively avoid the formation of a lubricating film between the abrasive and the sample surface due to the addition of lubricant (whether ethanol or oil), which reduces the cutting force of the abrasive, so that the scratches left by the 2000# sandpaper cannot be completely removed within the predetermined time. These scratches that have not been removed will become "inheritance" and be brought into the polishing stage, and the polishing liquid will be difficult to remove such deep scratches, finally leaving obvious defects on the mirror surface. The applicant found through long-term experiments that if the grinding time is too long and / or the force acting on the sample surface pressure rod is too large, not only the scratches are removed, but also the sample body is removed, wasting the sample and possibly changing the microstructure morphology. And excessive pressure will press the fine abrasive particles into the soft cement phase, or produce impact on the material, forming micro-cracks. If the grinding time is too short, the scratches of the 2000# sandpaper cannot be completely removed, and the deep scratches will be left to the polishing stage and become permanent defects. If the pressure is too small, the abrasive will not be able to effectively cut due to insufficient cutting force, but only slide on the surface, and the original scratches cannot be removed, making the fine grinding step meaningless.
[0025] Preferably, as an improvement, in the S8 polishing, short pile polishing cloth is used, and 1000 nm and 500 nm particle size diamond suspensions are used in turn for polishing, the polishing time is 120 s to 240 s, and the force of the pressure rod acting on the sample surface is 10 to 20 N.
[0026] Technical effects: The above-mentioned settings are adopted in the scheme, so that the fine scratches left in the fine grinding process can be completely removed, so as to obtain a flat, smooth and scratch-free surface for subsequent high-precision and high-definition backscattered electron imaging. The polishing time and pressure parameters defined in the scheme are particularly suitable for cement concrete samples. Cement concrete is a multiphase composite system, and the microstructure and composition, micro mechanics, hardness and other properties of different phases (such as calcium ferrite, calcium silicate, hydrated calcium silicate, calcium hydroxide, aggregate and steel bars) are different. Therefore, the effect of polishing is only to eliminate the fine scratches left on the surface during fine grinding, and the polishing time should not be shorter than 120 s, otherwise the surface scratches will not be completely eliminated; at the same time, the polishing time should not be longer than 240 s, otherwise it will be easy to cause cracking, and the interface step problem caused by different degrees of removal of different hardness materials.
[0027] Preferably, as an improvement, the scheme also provides a cement concrete backscattered electron image analysis sample prepared by the above-mentioned method. BRIEF DESCRIPTION OF DRAWINGS
[0028] Figure 1 It is a flowchart of the cement concrete backscattered electron image analysis sample preparation method in the embodiments of the present application.
[0029] Figure 2 It is a backscattered electron image of the cement sample prepared in Embodiment 1 of the present application.
[0030] Figure 3 It is a backscattered electron image of the cement sample prepared by the existing method in Comparative Example 1 of the present application.
[0031] Figure 4 It is a backscattered electron image of the polymer cement sample prepared in Experimental Group 2 of the present application.
[0032] Figure 5 It is a backscattered electron image of the polymer cement sample prepared in Experimental Group 3 of the present application.
[0033] Figure 6 It is a backscattered electron image of the polymer cement sample prepared in Comparative Group 2 of the present application.
[0034] Figure 7 It is a backscattered electron image of the polymer cement sample prepared in Comparative Group 3 of the present application.
[0035] Figure 8 Backscattered electron image of the polymer cement sample prepared for Comparative Group 4 of the present application.
[0036] Figure 9 Backscattered electron image of the polymer cement sample prepared for Comparative Group 5 of the present application.
[0037] Figure 10 Backscattered electron image of the polymer cement sample prepared for Comparative Group 6 of the present application.
[0038] Figure 11 Backscattered electron image of the polymer cement sample prepared for Comparative Group 7 of the present application.
[0039] Figure 12 Backscattered electron image of the polymer cement sample prepared for Comparative Group 8 of the present application.
[0040] Figure 13 Backscattered electron image of the polymer cement sample prepared for Comparative Group 9 of the present application.
[0041] Figure 14 Backscattered electron image of the polymer cement sample prepared for Comparative Group 10 of the present application.
[0042] Figure 15 Backscattered electron image of the polymer cement sample prepared for Comparative Group 11 of the present application. DETAILED DESCRIPTION
[0043] The present application will be further described in conjunction with the following examples, but the embodiments of the present application are not limited thereto. If not specifically indicated, the technical means used in the following examples and experimental examples are the conventional means known to those skilled in the art, and the materials, reagents, etc. used can be obtained from commercial channels.
[0044] Example 1 The present scheme provides a method for preparing a cement concrete backscattered electron image analysis sample, and a flowchart is shown in FIG. 1. Figure 1 The specific steps are as follows: S1, obtaining a sample: according to the formula, a polymer modified cement is prepared, and after curing for 28 days, the cement is crushed, and two pieces of 10 mm size fragments are taken; S2, terminating hydration and low-temperature drying (corresponding to Figure 1 terminating hydration + low-temperature baking in the present scheme): the fragment sample is soaked in anhydrous ethanol liquid bottle, the bottle is sealed and stored, the anhydrous ethanol in the bottle is poured out after 1 day and 3 days, and new anhydrous ethanol is injected, and the sample is taken out after 7 days; drying is carried out in an oven, the oven temperature is set to 50°C, and the drying time is 24 h; S3, sandpaper pre-polishing: after drying, the sample was taken out and pre-polished with 320# sandpaper to expose a new and flat surface of the sample; S4, resin inlaying: the mold was cleaned and release agent was applied to the inner surface of the mold; the pre-polished sample was placed in the mold with the pre-polished surface facing down; EpoThin2 epoxy resin was prepared according to a ratio of 100:45; then the vacuum cold inlaying machine was pre-vacuumed, and after the vacuum value reached the required value, inlaying was performed; the mold was left to stand in the laboratory for 24 h.
[0045] S5, sandpaper rough polishing: the mold was removed, and first 800# sandpaper was used for polishing for 45 s; then 1200#, 1500# and 2000# sandpaper were used for polishing the sample for 60 s, and the pressure of the pressure rod acting on the surface of the sample was 15 N; S6, secondary low-temperature drying (corresponding to Figure 1 the second low-temperature baking in the middle): the surface of the sample was cleaned with anhydrous ethanol, and the sample was dried in an oven at a temperature of 40℃ for 6 h.
[0046] S7, sandpaper fine polishing: 2500#, 3000# and 4000# sandpaper were used for fine polishing, and each type of sandpaper was polished for 40 s, and the pressure of the pressure rod acting on the surface of the sample was 15 N; S8, fine polishing: the sample was polished with a polishing cloth, and the polishing liquid particle size was 1000 nm and 500 nm, the polishing time was 120 s, and the pressure acting on the surface of the sample was 15 N; S9, final cleaning: after polishing, the surface of the sample was cleaned with anhydrous ethanol to obtain a smooth and flat backscattered electron image analysis sample.
[0047] Comparative Example 1 The cement sample for backscattered electron image prepared by the traditional method. It includes the following steps: 1, preparation of cement sample and curing; 2, termination of hydration, soaking in anhydrous ethanol for 7 days; 3, pre-polishing; 4, epoxy resin inlaying; 5, sandpaper polishing, from 800#, 1200#, 1500#, 2000#; 6, polishing, in turn from 3 μm, 1 μm, 0.5 μm; 7, anhydrous ethanol cleaning.
[0048] Experimental Example 1: Effect comparison The samples prepared in Example 1 and Comparative Example 1 were tested by FEI QUANTA FEG 650 environmental scanning electron microscope, and the results are shown in Figures 2-3 .
[0049] Figure 2The backscattered electron image of the polymer cement sample prepared by the method in the present solution in Example 1 is shown, and the image is clear without cracks, clearly showing the analysis of unhydrated cement particles, hydrated calcium silicate, calcium hydroxide and other hydration products and pores in the sample.
[0050] Figure 3 The backscattered electron image of the polymer cement sample prepared by the traditional method in Comparative Example 1 is shown, and a large number of microcracks are generated in the image, which significantly affects the analysis and statistics of the hydration products.
[0051] Experimental Example 2: Influence of Key Factors Experimental Groups 2-3 and Comparative Groups 2-11 show the influence of different factors in the method of the present solution on the analysis of the backscattered electron image of the cement concrete sample prepared finally, and the specific experimental design is shown in Table 1.
[0052] Table 1: Experimental design in Experimental Groups 2-3 and Comparative Groups 2-11
[0053] Experimental Example 2: Effect Comparison The samples prepared in Experimental Groups 2-3 and Comparative Groups 2-11 were tested by FEI QUANTA FEG 650 environmental scanning electron microscope, and the results are shown in Figures 4-15 .
[0054] Figure 4 The backscattered electron image of the polymer cement sample prepared by the method in the present solution in Experimental Group 2 is shown, and the image is clear without cracks, clearly showing the analysis of unhydrated cement particles, hydrated calcium silicate, calcium hydroxide and other hydration products and pores in the sample.
[0055] Figure 5 The backscattered electron image of the polymer cement sample prepared by the method in the present solution in Experimental Group 3 is shown, and the image is clear without cracks, clearly showing the analysis of unhydrated cement particles, hydrated calcium silicate, calcium hydroxide and other hydration products and pores in the sample.
[0056] Figure 6 The backscattered electron image of the polymer cement sample prepared by the different processing sequence combination (ethanol immersion-drying-immersion-drying-embedding-polishing-polishing-water-free ethanol cleaning) in the present solution in Comparative Group 2 is shown, and a large number of microcracks are generated in the image, which significantly affects the analysis and statistics of the hydration products.
[0057] Figure 7The backscattered electron images of the polymer cement samples prepared by comparative group 3 using different processing sequence combinations (ethanol soaking-drying-soaking-drying inlaying-polishing-absolute ethanol cleaning) of the present solution show that a large number of microcracks are generated in the images, which significantly affect the analysis and statistics of the hydration products.
[0058] Figure 8 The backscattered electron images of the polymer cement samples prepared by comparative group 4 using different parameter conditions (too low drying temperature in S2 / S6, and using super 800# sandpaper in S3 coarse grinding) of the present solution show that the inlaying depth of the epoxy resin with the surface obtained by using super 800# sandpaper in S3 coarse grinding and fine sandpaper polishing is shallow, which cannot play the supporting role of the epoxy resin on the sample, resulting in particle shedding in subsequent polishing and affecting the accuracy of the analysis results.
[0059] Figure 9 The backscattered electron images of the polymer cement samples prepared by comparative group 5 using different parameter conditions (too high drying temperature in S2 / S6, and using super 800# sandpaper in S3 coarse grinding) of the present solution show that a large number of microcracks are generated in the images, which significantly affect the analysis and statistics of the hydration products.
[0060] Figure 10 The backscattered electron images of the polymer cement samples prepared by comparative group 6 using different parameter conditions (using super 800# sandpaper in S3 coarse grinding) of the present solution show that the epoxy resin particles are shed and the cement surface pores are exposed, which affect the accuracy of the analysis results.
[0061] Figure 11 The backscattered electron images of the polymer cement samples prepared by comparative group 7 using different parameter conditions (using high viscosity epoxy resin in S4) of the present solution show that the sample is cracked from the inside, which affects the accuracy of the analysis results.
[0062] Figure 12 The backscattered electron images of the polymer cement samples prepared by comparative group 8 using different parameter conditions (too small force in S5 coarse grinding) of the present solution show that the sample surface is left with rough scratches that have not been removed, which affects the accuracy of the analysis results.
[0063] Figure 13 The backscattered electron images of the polymer cement samples prepared by comparative group 9 using different parameter conditions (too large force in S5 coarse grinding) of the present solution show that the sample is cracked from the inside, which affects the accuracy of the analysis results.
[0064] Figure 14The backscattered electron images of the polymer cement samples prepared by comparative group 10 using different parameter conditions (S7 fine grinding with too small force) of the scheme show that the residual coarse scratches on the sample surface are not removed, affecting the accuracy of the analysis results.
[0065] Figure 15 The backscattered electron images of the polymer cement samples prepared by comparative group 11 using different parameter conditions (S7 fine grinding with too large force) of the scheme show that the sample layer is ground off, affecting the accuracy of the analysis results.
[0066] In summary, the scheme can avoid the cracking of cement concrete samples caused by traditional methods by sequentially processing the cement samples with "terminating hydration and low-temperature drying-pre-grinding-inlaying-coarse grinding-secondary low-temperature drying-fine grinding-polishing-final cleaning", obtaining a smooth, smooth, scratch-free and crack-free sample, and then obtaining a high-quality backscattered electron image. First, the scheme carefully obtains and cleans the sample through pretreatment (including S1 sampling, S2 terminating hydration and low-temperature drying, and S3 pre-grinding), avoiding the introduction of new damage; secondly, in S4 inlaying, through the "vacuum + low-viscosity epoxy resin + cold inlaying" trinity, the brittle porous sample is fundamentally strengthened, the internal micro-cracks are bonded, the core is reinforced, and the "anti-cracking" cornerstone is laid. Subsequently, through the gradual progressive finishing of S5 coarse grinding, S6 secondary low-temperature drying, S7 fine grinding and S8 polishing, through the coarse-to-fine grinding and polishing steps, each step only creates better conditions for the next step, gradually reduces the large range of mechanical stress and thermal stress to the minimum, and finally obtains a stress-free, scratch-free surface.
[0067] The above is only an embodiment of the present application, and the specific technical solutions and / or common knowledge of the scheme are not described in detail. It should be noted that for those skilled in the art, without departing from the technical scheme of the present application, a number of modifications and improvements can be made, which should also be considered as the protection scope of the present application, which will not affect the effect and practicality of the patent. The protection scope claimed in this application should be subject to the content of its claims, and the specific implementation mode and the like in the specification can be used to explain the content of the claims.
Claims
1. A method of sample preparation for cement concrete backscattered electron image analysis, characterized by: It comprises the following steps: S1, obtaining a sample: sampling of cement concrete, crushing to a suitable size, and obtaining a sample; S2, terminating hydration and low-temperature drying: placing the sample obtained in S1 in anhydrous ethanol or isopropanol for immersion and low-temperature drying; S3, pre-polishing: pre-polishing the dried sample in S2 using coarse sandpaper; S4, embedding: embedding the pre-polished sample in S3 with low-viscosity epoxy resin in a vacuum cold-embedding device; S5, rough polishing: polishing the sample after the epoxy resin in S4 is cured by using 800#, 1200#, 1500#, and 2000# sandpaper in sequence; S6, secondary low-temperature drying: wiping the surface of the polished sample in S5 clean with anhydrous ethanol and then low-temperature drying; S7, fine polishing: fine polishing the dried sample in S6 by using 2500#, 3000#, and 4000# sandpaper in sequence; S8, polishing: polishing the fine-polished sample in S7 by using 1000 nm and 500 nm polishing liquid in sequence; S9, final cleaning: wiping the surface of the polished sample in S8 clean with anhydrous ethanol to obtain a sample for backscattered electron image analysis with a smooth and flat surface.
2. A method of preparing a sample for cement concrete backscattered electron image analysis according to claim 1, characterised in that: In S1, the sample is a block sample, the thickness of the block sample is less than 10 mm, and the length and width are both less than 15 mm.
3. A method of sample preparation for cement concrete backscattered electron image analysis according to claim 2, characterised in that: In S2, the immersion time is 5-7 days, and the anhydrous ethanol or isopropanol is replaced on the first day and the third day.
4. The method for preparing a sample for cement concrete backscattered electron image analysis according to claim 3, characterized in that: In S2, the low-temperature drying is performed in a low-temperature oven, the drying temperature is 40-60℃, and the drying time is 12-24h.
5. A method of preparing a sample for cement concrete backscattered electron image analysis according to claim 4, characterised in that: In S6, the low-temperature drying is performed in a low-temperature oven, the drying temperature is 40-60℃, and the drying time is 4-6h.
6. The method for preparing a sample for cement concrete backscattered electron image analysis according to claim 5, characterized in that: In S3, the grit of the coarse sandpaper is lower than 800#; the pre-polishing exposes the region of interest in the sample and obtains a larger flat surface.
7. A method of preparing a sample for cement concrete backscattered electron image analysis according to claim 6, characterised in that: In S4, the low-viscosity epoxy resin includes any one of EpoThin2, EpoKwick, and EpoxiCure; when used, the curing system is prepared according to the ratio of epoxy resin to curing agent of 100:40-50.
8. The method of claim 7, wherein the method further comprises: In S5, the purpose of the 800# sandpaper is to grind off a layer of epoxy resin on the surface to expose the pre-polished surface of the sample, and the polishing time is determined according to the thickness of the epoxy resin on the sample surface; the polishing time of 1200#, 1500#, and 2000# sandpaper is 30-60s, and the force of the pressure rod acting on the sample surface is 10-20N. 9. A method of preparing a sample for cement concrete backscattered electron image analysis according to claim 8, characterised in that: In S7, during the fine polishing process using 2500#, 3000#, and 4000# sandpaper, no anhydrous ethanol or oil is added, the grinding time is 30-60s, and the force of the pressure rod acting on the sample surface is 10-20N.
10. A cement concrete backscattered electron image analysis sample, characterized by: The sample is prepared by the method of any one of claims 1-9.